Indonesian Labor Sector During Covid-19 : Weighing the Impact of Company Saving Policy and Workers Protection - Sudiarawan, Kadek Agus; Yustisia Utami, Putu Devi; Angga Saputra, Gede Agus; Karunian, Alia Yofira (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 9 No 4 (2020), 2020)
The COVID-19 pandemic has a very significant impact on the global economy, especially in the business sector, which has suffered significant losses. On this matter it is deemed necessary to carry out research with the objectives first , to determine whether the policies implemented by companies in the form of employment termination and temporary workers layoff in order to survive the company can be legally justified, second , to determine what forms of legal protection should be obtained by workers in an industrial relationship with companies amidst of COVID-19, and third , to determine what forms of work relations/alternative policy models that can be offered to companies to be able to ease the burden on the company while being able to provide protection for workers amidst COVID-19. Research method that is applied is normative legal research with a statutory approach and legal concepts. The results show that company policies in the form of layoffs during the COVID-19 pandemic can be justified as long as they comply with the provisions of Article 163 to Article 165 of the Manpower Law, the act of laying off workers can be justified as long as it complies the provisions of the Minister of Manpower Circular Letter Number 5/1998 and Minister of Manpower Circular Letter Number 907/2004. Legal protection that shall be obtained if a worker is laid off must comply with the provisions of Article 156 of the Manpower Law. Companies can implement an industrial relationship by implementing Work From Home (WFH) during the COVID-19 pandemic.